2018
DOI: 10.1155/2018/3163096
|View full text |Cite
|
Sign up to set email alerts
|

Splinted and Nonsplinted Crowns with Different Implant Lengths in the Posterior Maxilla by Three-Dimensional Finite Element Analysis

Abstract: The aim of this study was to evaluate stress distribution in the implants/components and bone tissue for splinted and nonsplinted prostheses with different lengths of implants using three-dimensional finite element analysis. Six models from the posterior maxillary area were used in simulations. Each model simulated three Morse taper implants of 4.0 mm diameter with different lengths, which supported metal-ceramic crowns. An axial load of 400 N and an oblique load of 200 N were used as loading conditions. Splin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 29 publications
6
35
0
Order By: Relevance
“…This suggests that the overloading risk associated with NDIs under splinting conditions, specifically when connected by a dental bridge consisting of few dental units, as a FEA study already reported [15], would be comparable to that around RDIs. With this outcome, the capabilities of NDIs, which in FEA studies perform well for the replacement of single upper and lower second premolars, are extended [33].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This suggests that the overloading risk associated with NDIs under splinting conditions, specifically when connected by a dental bridge consisting of few dental units, as a FEA study already reported [15], would be comparable to that around RDIs. With this outcome, the capabilities of NDIs, which in FEA studies perform well for the replacement of single upper and lower second premolars, are extended [33].…”
Section: Discussionmentioning
confidence: 59%
“…Although splinted mini-implants (1.8 mm in diameter) compared with single miniimplants clinically show a similar bone loss [14], splinting of implants reduces the tensile stress in the posterior area of short fixed bridges [15]. Accordingly, the present study used FEA to determine whether the risks associated with NDIs could be decreased to a significant degree by the load-sharing effect resulting from the splinting concept.…”
Section: Introductionmentioning
confidence: 96%
“…Such restorations offer a more comfortable prosthetic approach with better emergence profiles and better oral hygiene access than other fixed partial restorations . However, a recent finite element analysis study recommends splinting of prostheses that favors better stress distribution . In a recent 3‐year prospective clinical study, short and standard implants supporting single and splinted crowns showed equal implant survival rates, peri‐implant conditions, and PBL .…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, these results must be interpreted with caution, since FEA cannot accurately predict the tissue response and adaptation mechanisms. Other studies suggest that different implant lengths are not relevant when evaluating the stress transmitted to the surrounding bone, if axial forces are applied [21,22]. The increased implant length translates into increased insertion torque value, higher Periotest values and theoretically significantly affected bone-to-implant contact (BIC) area.…”
Section: Discussionmentioning
confidence: 99%